Climate resilient product development from seaweeds kappaphycus alvarezii, gracilaria corticata and water hyacinth eichhornia crassipes - Shamiya Hasan (Academy of Climate Change Education and Research, 2018)
The work focuses on development of climate resilient products Biofuel and Biochar from Seaweeds and Water hyacinth as substrates. Compositional analysis including carbohydrate and cellulose content of Kappaphycus alvarezii, Gracilaria corticata and water hyacinth Eichhornia crassipes were done followed by pretreatment, hydrolysis and fermentation. Pretreatment was done with a concentration of 0.1% of hydrogen peroxide at two varying pH (4, 11.5), for a duration of 24 h at room temperature. Structural characterisation using FTIR, XRD and SEM were done to assess the effect of pretreatment. Acid hydrolysis was performed on the pretreated substrates and reducing sugars were further estimated. Fermentation of the substrates was carried out using yeast strain Saccharomyces cerevisiae. Bioethanol yield was estimated using HPLC analysis. The bioethanol content were detected in four samples (untreated G.corticata, G.corticata and E.crassipes treated at pH 4, and treated E. crassipes at pH 11.5). Further process optimization may provide optimum ethanol yield. Water hyacinth was converted into biochar in a muffle furnace in a pre-optimized condition of 300°C at 30 minute. The produced biochar was attempted for heavy metal remediation under lab conditions. The heavy metal analysis indicates efficacy of water hyacinth biochar in heavy metal removal. Additionally, phytoremediation of heavy metal was carried out using fresh rooted water hyacinth followed by analysis. The results indicates higher efficacy of water hyacinth in heavy metal removal from water. Implications of seaweed and water hyacinth based products have also been described through the work.